2006
DOI: 10.1007/s00134-006-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after acute respiratory distress syndrome: a meta-analysis

Abstract: ARDS survivors in different clinical settings experience similar decrements in QOL. The precise magnitude of these decrements helps clarify the long-term prognosis for ARDS survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
179
4
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(210 citation statements)
references
References 49 publications
15
179
4
12
Order By: Relevance
“…41 The most common scale used to measure the HRQOL of survivors of critical illness is the Medical Outcomes Study 36-Item Short Form Health Survey, Standard Form (SF-36). 42 This questionnaire consists of 36 items, which measure both physical health (physical function, physical role function, bodily pain, and general health) and mental health (vitality, social function, emotional function, and mental health).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…41 The most common scale used to measure the HRQOL of survivors of critical illness is the Medical Outcomes Study 36-Item Short Form Health Survey, Standard Form (SF-36). 42 This questionnaire consists of 36 items, which measure both physical health (physical function, physical role function, bodily pain, and general health) and mental health (vitality, social function, emotional function, and mental health).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Studies of critically ill patients hospitalized in the intensive care unit (ICU) for at least 7 days suggest that greater than one-fourth develop neuromuscular weakness attributable to the ICU stay (1)(2)(3)(4)(5)(6)(7)(8)(9). This disablement is associated with reductions in health-related quality of life, increased psychological distress, and delayed return to work (3)(4)(5)(6)(7)(8) with impairments persisting for years after the index hospitalization.…”
mentioning
confidence: 99%
“…For example, survivors of acute respiratory distress syndrome (ARDS) have prolonged 6-minute walk times, executive dysfunction, other neuropsychiatric deficits, and diminished ability to return to work (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Numerous studies have found quality of life among survivors of critical illness (14,15), severe sepsis (16,17), and ARDS (4-8, 13, 18) to be abnormally low.…”
mentioning
confidence: 99%